Graphene/SrTiO3 nanocomposites used as an effective electron-transporting layer for high-performance perovskite solar cells. Issue 64 (12th July 2015) - Wang, Chen; Tang, Ying; Hu, Yajing; Huang, Lu; Fu, Jianxun; Jin, Jing; Shi, Weimin; Wang, Linjun; Yang, Weiguang
<x xml:space="preserve">Abstract</x> The device based on graphene/SrTiO3 nanocomposites exhibited a PCE of 10% with a Jsc of 18.08 mA cm−2.